Compositional changes of rice straw fibers after pretreatment with diluted acetic acid: Towards enhanced biomethane production. (1st September 2019) - Peng, Jingjing; Abomohra, Abd El-Fatah; Elsayed, Mahdy; Zhang, Xiuzhi; Fan, Qizhou; Ai, Ping
Abstract: In the present study, diluted acetic acid was used for the pretreatment of rice straw in order to improve its bioconversion into biomethane. After pretreatment with 2% acetic acid for 24 h, cellulose and hemicellulose significantly reduced by 8.9% and 18.1%, respectively. The degradation of cellulose and hemicellulose resulted in significant increase of relative lignin ratio by 14.9%. Cumulative biomethane production after 28 days of anaerobic digestion of straw pretreated with 2%, 4% and 6% for 24 h was 24.3%, 15.2%, and 18.1%, respectively, higher than the untreated sample. Longer pretreatment for 36 and 48 h showed the same trend with relatively low biomethane yield. Thus, 24 h pretreatment with 2% acetic acid improved biomethanation over other pretreatments. Scanning electron microscopy and Fourier transform infrared spectroscopy confirmed the partial degradation of rice straw and modification of lignin structure by un-bonding the ether chain within lignin molecules as a result of pretreatment. Pretreatment with 2% acetic acid for 24 h resulted in the maximum biomethane energy yield of 6.29 MJ kg −1 dry straw, 47.3% energy conversion efficiency and the maximum net profit of US$ 106.4 ton −1 dry straw. In conclusion, application of 2% acetic acid for 24 h is a promising approach for high lignocellulose degradation efficiency at mild conditions due to the relatively short pretreatment time and enhanced biomethanation. Graphical abstract: Image 1 Highlights: Rice straw was pretreated by diluted acetic acid for different times. Application of 2% acetic acid for 24 h showed the maximum biomethane production. Acetic acid pretreatment resulted in significant changes in lignin structure. Long pretreatment time was detrimental due to loss of cellulose. Pretreatment with 2% acetic acid for 24 h showed the highest estimated net profit.